New butterfly records from the Jammu Shiwaliks, Jammu & Kashmir, India - Shakha Sharma; Neeraj Sharma (Journal of Threatened Taxa, 2017)
The Himalayan state of Jammu and Kashmir, owing to variety of habitats, different climatic regimes and a wide range of altitude offers conducive habitats to butterflies ranging from low level hills of Shiwaliks to Trans-Himalayan landscapes of Ladakh through mighty Pir-Panjal and Valley of Kashmir.   It is noteworthy that these mountainous landscapes though rich in insect diversity are the least known for butterfly fauna. The present note describes the new records based on opportunistic surveys of butterflies on the sidelines of avian surveys conducted in Jammu Shiwaliks during the years 2015 and 2016.